Perception of patients about professional performance and procedures performed in the pre, intra, and postoperative period of abdominoplasty - Natália Ligeiro Dos Santos; Iara Gama Esteves-De-Oliveira; Rogério Eduardo Tacani; Cristiano Schiavinato Baldan; Igor Fagioli Bordello Masson; Thiago Saikali Farcic; Aline Fernanda Perez Machado (Revista Brasileira de Cirurgia Plástica, 2020)
Introduction: abdominoplasty is the third most performed cosmetic surgery in Brazil. Its surgical planning involves the pre, intra, and postoperative moments with the performance of several specialized professionals. Therefore, the objective of this study was to analyze the patients' perception of their professional performance and the procedures performed before, during, and after the abdominoplasty. Methods: This is a cross-sectional and observational study. Data collection was done through an online questionnaire made available digitally to women aged between 18 and 60 years, who underwent abdominoplasty in the last 12 months. Results: A total of 376 patients answered the questionnaire; however, 22 were excluded, totaling 354 questionnaires answered. It was observed that 63.5% reported having undergone abdominoplasty due to skin flaccidity, 53.3% had undergone abdominoplasty associated with liposuction, 61% reported that they had not undergone preoperative procedures, 59.9% reported not knowing whether there was a physiotherapist in the operating room during the intraoperative period. , 70.6% of the patients underwent postoperative procedures, 37.4% of whom were physiotherapists, the most common complication being edema representing 84.2%. Conclusion: The main indication for abdominoplasty was sagging skin, which is most often associated with liposuction. Most of the patients did not undergo preoperative procedures. They were performed after 1 to 3 days after the operation, with a physiotherapist, on the advice of an acquaintance, often three times a week, due to the complaint of edema. The most performed procedures were manual lymphatic drainage and therapeutic ultrasound.